Case 3713: Scarabaeus ferrugineus Palisot de Beauvois, 1809 (currently Bradycinetulus ferrugineus) (Insecta: Coleoptera: Scarabaeoidea): proposed conservation of the specific name - Smith, Andrew B T; Paulsen, M J (Bulletin of Zoological Nomenclature, 2017)
The purpose of this application, under Article 23.9.5 of the Code, is to conserve the specific names Scarabaeus ferrugineus Olivier, 1789 (currently Metacatharsius ferrugineus) (Scarabaeidae) and Scarabaeus ferrugineus Palisot de Beauvois, 1809 (currently Bradycinetulus ferrugineus) (Geotrupidae). Although Scarabaeus ferrugineus Olivier, 1789 and Scarabaeus ferrugineus Palisot de Beauvois, 1809 are primary homonyms, they have not been treated as congeneric for almost 180 years and were both transferred out of the genus Scarabaeus Linnaeus, 1758 by 1845. Both names have been treated as valid since they were proposed. It is proposed that Scarabaeus ferrugineus Palisot de Beauvois, 1809 be conserved by ruling that it is not invalid by reason of being a junior homonym of Scarabaeus ferrugineus Olivier, 1789.
Keywords: Nomenclature; taxonomy; Scarabaeidae; Geotrupidae; Metacatharsius ferrugineus; Bradycinetulus ferrugineus; Scarabaeus ferrugineus; dung beetles; scarabs